CHROMATOGRAPHIC STUDIES ON BIOACTIVE COMPOUNDS OF ETHANOLIC LEAF EXTRACT OF AERVA LANATA BY HIGH PERFORMANCE THIN LAYER CHROMATOGRAPHY TECHNIQUE - Sounder, Lucia; Doss, Victor Arockia (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objective: This study was designed to determine the bioactive compounds such as alkaloids, glycosides, phenol, and tannins by high performance thin layer chromatography (HPTLC) which will help in crude drug identification and in the standardization of Aerva lanata in pharmacological industries. Methods: HPTLC studies were conducted as Harborne described. The toluene-acetone-formic acid (4.5:4.5:1); ethyl acetate-ethanol-water (10:1.35:1); ethyl acetate-ethanol-water (8:2:1.2); toluene-ethyl acetate-formic acid-methanol (3:3:0.8:0.2) were employed as mobile phase for phenol, alkaloid, glycoside, and tannin profiles. Result: The ethanolic extract of leaves of A. lanata illustrated the presence of 11 different types of phenol with 11 different Rf values with range 0.06- 0.95, 10 different types of alkaloid with 10 different Rf values from 0.02 to 0.92, 12 different types of glycoside with 12 different Rf values from 0.02 to 0.96, 9 different types of Tannin with 9 different Rf values from 0.07 to 0.93. Conclusion: This study supplements valuable information about known and unknown bioactive compounds with the bioactivity of A. lanata. Further, pharmacological studies on structure of the bioactive compounds can be formulated to treat diseases. Thus, the ethanolic extract of A. lanata plant can be utilized as a useful medicinal herb for alleviation of various illness and disorder. Â 